Positioning Persebaya Store Dalam Membentuk Fashion Lifestyle - Auzan, Fathoni Bayu (The Commercium, 2022)
This study aims to identify and describe the positioning of Persebaya Store in forming a fashion lifestyle, using case study methods and descriptive qualitative research types. Researchers conducted observations and interviews with the marketing communications division of the Persebaya Store, the shopkeeper of the Persebaya Store, and a Bonek from the journalist Emosijiwaku.com. Analysis of data findings based on indicators of positioning and communicating positioning through the marketing mix. The results of this study indicate that Persebaya Store is positioning to form a fashion lifestyle, through product design using a minimalist design that creates an elegant impression, so that it can be used flexibly. Persebaya Store makes local fashion brands a trend, inspiration on product design and promotional content creation. The establishment of the physical outlet Persebaya Store, apart from being a place of sale, is also used as a gathering place for Bonek with various concepts that are presented, with the aim of attracting the attention of consumers. The participation of the Surabaya Fashion Parade event allows Persebaya Store to position the brand in the minds of potential consumers that Persebaya Store's products are no less cool and can compete with other fashion brands.